Comparison of simple and active solar stills for freshwater recovery during lithium brine mining - Baspineiro, Celso Fernando (2024)
Lithium mining from brines raise environmental issues due to huge volumes of both saline and freshwater being constantly pumped in desertic environments. Data indicating the slow depletion of both underground water levels and lagoon surfaces in the regions where large lithium brine mining exploitations are located have recently being disclosed. Amongst different direct lithium extraction methodologies, DLE, for more sustainable lithium recovery, a few proposals aim at the recovery of freshwater from the high salinity brines. About 900 kg of freshwater could potentially be recovered per cubic meter of processed native brine. The water evaporation and freshwater production capabilities of a simple and an active solar still are compared in this work. These are two simple and relatively low-cost technologies that could be adapted to existing solar evaporation ponds. The two systems were thermodynamically modelled. Equations were derived which were fed with real meteorological data from the Olaroz salt lake location and brine properties derived from the Pitzer model for the said brine. Analysis of the heat fluxes show that the behavior of both systems is relatively similar with large heat losses that are responsible for neither of the systems reaching the evaporation rate of the evaporation ponds.